Waging peace : Israel and the Arabs, 1948-2003 - Rabinovich, Itamar, 1942- (Princeton University Press, 2004)
Considerably expanded to include the impact of the 2003 war in Iraq and its aftermath, this new edition of Waging Peace provides a unique insight into the critical debate on the future of peace in the Middle East. A former chief negotiator for Israel, noted scholar-diplomat Itamar Rabinovich examines the complete history of Arab-Israeli relations beginning in 1948. He then gives a vivid account of the peace processes of 1992-1996 and the more dispiriting record since then.